Human-animal chimerical transplantation in tissue engineering experimentation: exploring the ethical issues - Ahmad Radzi, Muhammad Aa’zamuddin; Hashi, Abdurezak Abdulahi; Zainuddin, Zainul Ibrahim; Abdul Rahman, Rozlin; Mohamad Sukri, Norhamiza; Md Nazir, Noorhidayah; Razali, Wan Ahmad Dzulkarnain; Sha'ban, Munirah (2015)
Tissue engineering and regenerative medicine (TERM) offers an alternative treatment modalities for damaged organs/tissues. Tapping cell-based therapy and autologous transplant approaches, this restorative technique aims at reconstructing human tissues/organs for transplantation. But, before it can be used clinically, tissue engineered construct (TEC) must undergo the pre-clinical validation protocol in selected animal models. For example, subcutaneous implantation of human TEC in the immunodeficient mice has been long used as a gold standard to ascertain the feasibility of TEC in vivo. However, laboratory studies involving this type of interspecies transplant or, classically known as “chimera” certainly raises multiple ethical issues. Unlike the three hybrid creatures in Greek mythology, the term in biomedical research can be defined as an individual, organ, or part consisting of tissues of diverse genetics constitution. Most chimeras are produced by introducing human stem cells into developing animal embryos/foetuses. However in TERM, the subcutaneous pocket of the mice serves as a host to provide internal microenvironment for TEC maturation. The TEC that forms is encapsulated, easily dissected, and do not dwell beyond the local mice tissue. The possibility for an extensive chimerism of the animal gonads or brain by human cells seems unlikely, especially considering the short experiment duration; typically less than 3-month. Therefore, this paper aims to identify harms and benefits of human-animal chimerical transplantation in biomedical application. Besides that, moral aspects of human dignity and animal rights will also be examined and discussed. Among those aspects that shall be explored include which tissues will be chimerized; the degree of chimerism that may result; and the state of physiologic integration of the implanted TEC into mice. There may be some questions which are left unanswered, but, in certain aspects animal model remains a necessity because of the complexity of a human system